Genetic diversity of Potamogeton pectinatus L. in Iran as revealed by ISSR markers - Abbasi, Shabnam; Afsharzadeh, Saeed; Saeidi, Hojjatollah (Acta Botanica Croatica, 2017)
Potamogeton pectinatus L. is a widespread aquatic species distributed widely in aquatic ecosystems of Iran. In this study, inter simple sequence repeat (ISSR) markers were used to assess the genetic diversity of 35 accessions and 175 individuals of P. pectinatus collected from different regions of Iran. In total, 123 polymorphic DNA fragments were amplified from five combinations of ISSR primers. The ISSR based principle coordinate analyses (PCoA) demonstrated four different groups mostly corresponding with their geographic origins (North, Kerman/Fars, Centre and Southwest). The most variable populations were found in the central region of Iran possibly as a consequence of the larger number of samples from that region. The result of molecular variance (AMOVA) attributed 11% of the total genetic variation among and 89% within population variation. The results showed high levels of intra-regional and low inter-regional gene flow between clones, although the Northern accessions were clearly differentiated from the others. There was a low correlation between genetic distance and geographic distance of accessions. The results of STRUCTURE analysis suggested the presence of three genetic groups of this species in Iran, mostly adapted to different ecological conditions. Our results cover one of the gaps of different studies worldwide. In addition, our results confirm high levels of genetic diversity of P. pectinatus in Iran.